The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1530/eje.0.1470085
|View full text |Cite
|
Sign up to set email alerts
|

The value of plasma markers for the clinical behaviour of phaeochromocytomas

Abstract: Objective: Phaeochromocytomas (PCCs) are widely known for their clinical unpredictability. This study intends to define predictive plasma markers for their variable postoperative behaviour. Furthermore, the diagnostic accuracy of these plasma tests was determined. Design and Methods: A retrospective correlative study was performed in a series of 83 operated and four autopsied patients in order to correlate preoperative catecholamine (CAT) levels of 103 PCCs with their clinical behaviour. In a subset of cases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
1
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 48 publications
5
72
1
3
Order By: Relevance
“…Our data also indicated that metastases were more common in norepinephrine-producing tumours than in epinephrine-producing tumours. PHEO/PGL tumours may exhibit different biochemical phenotypes because extra-adrenal tumours secrete predominantly norepinephrine whereas adrenal tumours secrete mainly epinephrine (van der Harst et al 2002). In this study 38.6% (49 of 127) of the adrenal tumours were norepinephrine type.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Our data also indicated that metastases were more common in norepinephrine-producing tumours than in epinephrine-producing tumours. PHEO/PGL tumours may exhibit different biochemical phenotypes because extra-adrenal tumours secrete predominantly norepinephrine whereas adrenal tumours secrete mainly epinephrine (van der Harst et al 2002). In this study 38.6% (49 of 127) of the adrenal tumours were norepinephrine type.…”
Section: Discussionmentioning
confidence: 46%
“…Norepinephrineproducing tumours lack PNMT (the enzyme that converts norepinephrine to epinephrine) and are considered to be less differentiated than epinephrine-producing tumours based on catecholamine synthesis. Dopamine hypersecretion was considered a feature of immaturity and a marker for malignant PCC/PGL (van der Harst et al 2002). …”
Section: Discussionmentioning
confidence: 99%
“…The most robust studies of the characterization of MPP patients at the time of the diagnosis have suggested that metastatic adrenal and extra-adrenal tumors occur at equal rates and that the survival rates of metastatic adrenal and extraadrenal tumors overlap (2); w60% of MPP patients have tumor burden-and hormone-related manifestations (e.g., pain, hypertension, and constipation) (3); most MPPs produce noradrenaline and normetanephrine and/or dopamine and methoxytyramine, which partly reflects the higher risk of malignancy associated with SDHB mutations and extra-adrenal locations (4,5,6,7,8); most MPP patients have apparently sporadic tumors or tumors associated with germline or somatic mutations of the succinate dehydrogenase subunit B (SHDB) gene (2,9,10). The high prevalence of SDHB mutations (30-50% of patients) supports the screening of all patients with MPPs for such mutations.…”
Section: Characterization Before Therapymentioning
confidence: 99%
“…Recent studies suggest that most if not all of the antihormonal actions of SRIF are mediated via either sstr2 and/or sstr5 (Lamberts et al 1996). SRIF receptors are expressed in a large number of tumors (Kennedy and Dluhy 1997;Hofland et al 1999;Kaltsas et al 2001;van der Harst et al 2001). Conformationally stabilized SRIF analogues, such as octreotide (which binds with high affinity to sstr2 and -5), are used clinically to control humoral hypersecretion and tumor growth in patients with acromegaly, carcinoids, and pheochromocytomas (Berlowitz 1995).…”
Section: Discussionmentioning
confidence: 99%